Analysis of implementation of trade secret legal protection in franchise businesses - Karmana, Gadis Reyatezar; Septiani, Dini; Waskim, Waskim; Rahman, Alip; Dikrurahman, Diky (International Journal Labs, 2024)
Franchising has significant potential but also high risks due to trade secret violations. Law Number 30 of 2000 regulates trade secrets, but these violations can be detrimental to the party providing the secret. Research on the feasibility of establishing legal protection for trade secrets in franchise companies is crucial. This research aims to examine how franchise businesses have used trade secret legal protections. A qualitative methodology was used, and data collection techniques involved collecting relevant documents. The findings indicate that if trade secrets meet the criteria regulated in Article 1 Paragraph 1 of the Trade Secrets Law, they are entitled to legal protection. Violations may result in criminal sanctions, including imprisonment for up to 2 years or a fine of up to Rp. 300 million.